Juridical Analysis Of Cyber Crime Against Children - Ririn Nurfaathirany Heri; Heri Tahir; Realizhar Adillah Kharisma (Cita konsultindo, 2024)
Technology is a double-edged sword for society, because apart from contributing to increasing welfare, progress and human civilization, it is also an effective means of committing crime. The aim of this research is to determine the development of crimes involving children in cyberspace (cyber crime) and to determine efforts handling children involved in crimes in the virtual world (Cyber Crime). This research method is normative-empirical research, a library study located in online libraries and physical libraries and direct research in several schools in Makassar City. This research uses a qualitative descriptive model/method. The data collection techniques used are interview techniques and literature study. Meanwhile, the data analysis technique used is qualitative descriptive analysis. The results of the research show that handling of children involved in cybercrime needs to be carried out carefully with an approach that focuses on rehabilitation, education and recovery rather than punishment. The approach intended for handling children involved in cybercrime cases is a Restorative Approach, Psychological Counseling and Therapy, Digital Literacy Education, Rehabilitation Programs and Special Development, diverting children's interests to productive activities. Collaboration with Parents and Schools and finally a Legal Approach that is Compliant with Child Protection. In conclusion, an approach that prioritizes education, rehabilitation and involvement of related parties can help children get out of a negative environment and improve behavior.